Minangkabau's Adat Law Reflected In Abdulkarim Khiratullah's Novel Mencari Cinta Yang Hilang - zakia, Putri (Program Pascasarjana IAIN Langsa, 2021)
Minangkabau's Adat law has developed for centuries. In its development, Minangkabau's Adat law has given significant contributions to the dynamics and the continuity of Minangkabau's society. Minangkabau's society is matrilineal; it is not patriarchal in which the chief of a clan is always a man. In matrilineal, the women of the clan will be the chief and they can sack men if they do not do a good job. This paper studies first, what the types of Minangkabau's Adat laws are reflected in the novel; second, how the implementations of Minangkabau's Adat laws are in the novel. This study focuses on the analysis of Minangkabau's Adat law reflected in Abdulkarim Khiratullah's novel Mencari Cinta yang Hilang. As the research design is very crucial to conducting a research, this study applied descriptive qualitative research as its research design. It is important to carry out this research because it has fascinated many researchers due to the co-existence of contradictory elements with Islamic regulation like matrilineal family structure, marriage system and inheritance regulations.